Study and application for rotational speed estimation method of a sensorless DC motor using adaptive filter - M Ramli, Roshahliza (2010)
When performing speed control of a sensorless Dc motor with brushes, it is necessary to estimate the rotational speed by a certain method. Theoretically, if the relation based on the fact that the fundamental frequency of the ripple superimposed on the supply current of DC motor with brushes is proportional to rotational speed is used, estimation of rotational speed is possible. However, besides a fundamental wave component, there are comparatively loud harmonicscomponents and noises which are existed in the ripple contained in the supply current of the motor, so it is not easy to estimate fundamental frequency of the ripple. Moveover, in this research, it aims the control of the rotational speed of the motor, so estimation of rotational speed in real time must be performed. Therefore, using the adptive line enhancer (ALE: Adaptive Line Enhancer), estimation of the rotational speed of a motor was examined. In the research, using ALE with the second-order of band pass type IIR filter,estimation of the rotational speed of a motor was considered. It becomes a problem in the case that, besides noises, thera are also higher harmonics componentscontained in the ripple superimposed on the supply current of the motor. As the result of examination by a simulation, because of higher harmonic components may remain of the feedback path which controls the coefficient of a filter, the error of the estimated rotational speed became large, and futhermore, it turned out that the variance also became larger. Therefore, in order to reduce the harmonic components, inserting a low pass filter in a feedback path was proposed method, it was confirmed that the error of the estimated rotational speed and the variance became smaller. Next, the actual ripple of the supply cureent of DC motor was acquired, and then inputted into ALE, and the rotational speed of the motor was estimated. When the value of the step size parameter of ALE was set up appropriately, rotational speed has been estimated in sufficiently high accuracy. However, high accuracy of rotational speed was not acquired when the value of the step size parameter of ALE was changed about a decimal from this value. Many thingswere examined in order to solve this problem. As the result, if bandwidht of the band-pass filter of ALE is made large, it turned out that rotational speed can be estimated in sufficient accuracy, even if the value of the step size parameter of Ale was change about a decimal from the suitable value.